(untitled) (Práxis Educativa, 2022)
The article seeks to analyze the impact that the closure of non-graded schools and the associated concentration measures (construction of graded schools) had on a geographical area of ​​mainland Portugal - Pinhal Interior Sul (PIS), a low-density rural territory -, at the beginning of the 21st century. Mobilizing a set of statistical sources (demographic and educational) and using educational municipal policy papers the goal was to understand whether this process followed social, economic, and pedagogical reasons based on the idea of ​​rural development in an integrated perspective. In the end, what development vision was conveyed? What can be concluded is that nor only the retreat of the rural world didn´t happen (in fact, it has intensified) nor the graded school typology didn’t seem to have increased the pedagogical capacity of schools. Keywords: Portugal. Pinhal Interior Sul. Graded school. Rural school. Educational municipal policy paper.